Development of aeration devices and feeding frequencies for oxygen concentration improvement in 60-tones freshwater recirculating aquaculture and biofloc ponds of Asian seabass (Lates calcarifer) rearing. (November 2022) - Whangchai, Niwooti; Klahan, Rungkan; Balakrishnan, Deepanraj; Unpaprom, Yuwalee; Ramaraj, Rameshprabu; Pimpimol, Tipsukhon
Abstract: This research aimed to improve the technique to maintain the oxygen content of two freshwater Asian sea bass ( Lates calcarifer ) culture systems (recirculating aquaculture system; RAS; and biofloc system; Floc). The dissolved oxygen content was increased by using a blower with flexible rubber hose aerators. For the first study, the effectiveness of oxygenation was investigated. As a result, the aerator and flexible rubber hose are appropriate for increasing oxygen levels in the fish pond. An air pump with a flexible aeration tube (400 W), one set of ejector aerators (250 W), and two sets of ejector aerators (250 × 2 W) were used to test the efficiency of oxygenation. In addition, the performance of the RAS and Floc systems, off-flavor (geosmin and MIB) in taints, and economic returns were assessed. This study found that after monitoring two 60-tonne concrete ponds with one set of blowers (RAS1) and two sets of blowers (RAS2) connected by a flexible rubber tube; feeding frequency (2 and 6 times/day). However, daily dissolved oxygen fluctuated in the RAS, and this value went to its lowest after post-feeding. Dissolved oxygen was higher than the two-meal pack per day when the feeding was expanded to six meals. This aeration device could provide dissolved oxygen enough for 900 kg fish/400 W. Seabass raised in the freshwater RAS system had higher yields and growth rates than those raised in the biofloc pond systems. In addition, low off-flavors trained was observed. Therefore, this research could improve aeration management by aeration devices and increase feeding frequency while developing freshwater-adapted Asian seabass production. Graphical abstract: Image 1 Highlights: RAS and biofloc technology using biological sludge as a biorefinery approach. Asian sea bass reared with novel aeration devices and feeding frequencies. Oxygen concentration was effectively used with bubbling methods. RAS and biofloc systems were shown to be suitable for freshwater seabass culture.